THE WELL-BEING OF MICRO SMALL AND MEDIUM ENTERPRISES’ PRACTITIONER IN COVID-19 PANDEMIC - Diana Harding; Deris Friyanto; Kevin Muhamad Lukman (Universitas Padjadjaran, 2022)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays an important role in the development of a country, providing massive revenues and employment opportunities. However, the challenges of MSMEs sector are now exacerbated with the situation of COVID-19 due to the business limitation and degrading economic situation. In addition to financial difficulties, there is also the concern on the well-being of MSMEs practitioners which can influence the sustainability of the sector. This research was conducted with the purpose of investigating the level of well-being for MSMEs practitioners. The approach of subjective well-being using Satisfaction with Life Scale (SWLS) and scale of positive and negative experience (SPANE) were implemented in a form of questionnaire. A total of 119 MSMEs practitioners were collected in this study, with their level of well-being investigated, as well as the challenges and innovations experienced during the COVID-19 pandemic. The findings in this study show that the MSMEs practitioners under association support were majority within medium and high levels of well-being, however this study also takes note of practitioners within low-level of well-being. Hence there is the implication challenge to formulate policy intervention to support MSMEs sector which integrate the financial and mental health aspect to maintain the sustainability of the sector.